Comparison of the effects of thermal stress and CO2-driven acidified seawater on fertilization in coral Acropora digitifera. Issue 4 (22nd May 2014) - Iguchi, Akira; Suzuki, Atsushi; Sakai, Kazuhiko; Nojiri, Yukihiro
Summary: Global warming (GW) and ocean acidification (OA) have been recognized as severe threats for reef-building corals that support coral reef ecosystems, but these effects on the early life history stage of corals are relatively unknown compared with the effects on calcification of adult corals. In this study, we evaluated the effects of thermal stress and CO2 -driven acidified seawater on fertilization in a reef-building coral, Acropora digitifera. The fertilization rates of A. digitifera decreased in response to thermal stress compared with those under normal seawater conditions. In contrast, the changes of fertilization rates were not evident in the acidified seawater. Generalized Linear Mixed Model (GLMM) predicted that sperm/egg crosses and temperature were explanatory variables in the best-fitted model for the fertilization data. In the best model, interactions between thermal stress and acidified seawater on the fertilization rates were not selected. Our results suggested that coral fertilization is more sensitive to future GW than OA. Taking into consideration the previous finding that sperm motility of A. digitifera was decreased by acidified seawater, the decrease in coral cover followed by that of sperm concentration might cause the interacting effects of GW and OA on coral fertilization.